The Relationship between Obesity and The Incidence of Gastroesophageal Reflux Disease (GERD) - Puput S; Syamsu Rijal; Nur Aulia Amir (International Medical Journal Corp. Ltd, 2025)
Background: Gastroesophageal Reflux Disease (GERD) is an upper gastrointestinal disorder frequently associated with obesity. The prevalence of both GERD and obesity continues to rise in Indonesia, highlighting the importance of understanding their epidemiological relationship to support prevention and management strategies. Methods: This study is a narrative literature review that identifies and analyzes scientific publications from 2020–2025 regarding the relationship between obesity and the incidence of GERD in Indonesia. Literature was searched through PubMed, ScienceDirect, Google Scholar, and Garuda Ristek-BRIN using relevant keywords. Empirical and relevant articles were selected and analyzed qualitatively. Results: The majority of studies found a significant association between increased Body Mass Index (BMI) and the risk of GERD. The main mechanisms include increased intra-abdominal pressure due to visceral fat accumulation and dysfunction of the lower esophageal sphincter (LES), which facilitates gastric acid reflux. Some studies reported an odds ratio for GERD risk in obese individuals reaching up to 9.44 times compared to those with normal weight. Additionally, high-calorie and high-fat diets were shown to exacerbate GERD symptoms. Although some studies reported less significant findings, the general consensus supports obesity as a major risk factor for GERD. Conclusion: Obesity significantly increases the risk of GERD through physiological and hormonal mechanisms. Therefore, weight management through lifestyle modification and nutritional intervention is a crucial strategy for the prevention and treatment of GERD in the adult population in Indonesia.